How People Perceived Heirlooms as Sources of Environmental Values: Magic’s Frazer Theory on The Jamasan Ritual - Fardan Mahmudatul Imamah; Intan Pebriyani (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2023)
The magical side of the jamasan ritual is often put aside to save the impression of the jamasan ritual as a result of the label of syncretism between Java and Islam. Because instead of being considered a 'religious ritual', jamasan is part of Javanese culture which is separated from their beliefs. However, academics need to pay attention to another part of the jamasan process to extract how this ritual holds various environmental values that shape the mindset and identity of the community. This research aims to explain how (1) the magical side of the Jamasan ritual can build a 'logical' rhetoric of Javanese beliefs. In addition, (2) how the belief in the sanctified objects as heirlooms has implications for the transfer of values of respect for the environment in which the Javanese live. This research takes a case study of the Jamasan Kiai Ngaliman Ritual in the Nganjuk Regency, using James George Frazer's magical theory approach and ethnographic methods for data collection. As a result, awareness of the people's attachment to their ancestors through heirlooms becomes a medium for how they 'communicate' with the surrounding nature. This awareness is reminiscent of their location in the mountains, which relies on good natural conditions for agriculture, plantations, stable soil and water intake, and avoidance covid virus and other natural disasters. This attachment to ancestors is valuable in maintaining the stability of social cohesion to understand the surrounding nature.